2019
DOI: 10.1038/s41598-019-54779-7
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Ear Abnormality from 2D Photographs Using Convolutional Neural Networks

Abstract: Quantifying ear deformity using linear measurements and mathematical modeling is difficult due to the ear’s complex shape. Machine learning techniques, such as convolutional neural networks (CNNs), are well-suited for this role. CNNs are deep learning methods capable of finding complex patterns from medical images, automatically building solution models capable of machine diagnosis. In this study, we applied CNN to automatically identify ear deformity from 2D photographs. Institutional review board (IRB) appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…Deep learning has been widely used in various fields. Among the many deep learning models, CNNs are the most efficient 6 . CNNs have shown excellent results in the analysis of radiographic images when compared to the results by medical experts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deep learning has been widely used in various fields. Among the many deep learning models, CNNs are the most efficient 6 . CNNs have shown excellent results in the analysis of radiographic images when compared to the results by medical experts.…”
Section: Discussionmentioning
confidence: 99%
“…CNNs have shown excellent results in the analysis of radiographic images when compared to the results by medical experts. Previous studies have shown that deep learning can be used to recognize anatomical structures, find anomalies, measure the distance, and classify structures in medical images 1,[3][4][5][6][7][8][9][10][11][12][13][14][15] . However, in most studies, object detection was conducted manually, and tasks were limited to performing simple measurements, comparisons, or classifications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, nonsurgical techniques have been used to correct ear deformity, such as splinting and ear molding 3 . These techniques are noninvasive, painless, and avoid morbidities that can be associated with traditional otoplasty 4 , 5 . The range of deformities that are treatable with neonatal molding is distinct from those congenital deformities that result from hypoplasia of skin or cartilage, which generally require surgical correction 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…CNN is a deep learning method that has had great success in medical image analysis to classify and analyze diseases and is a promising solution to assess ear deformity and treatment outcomes 5 . In addition, its application has been successful in ear recognition 10 – 12 and has shown to be superior to traditional computer vision systems that uses feature extraction algorithm such as principal component analysis, speeded up robust features 11 , or even handcrafted features 13 .…”
Section: Introductionmentioning
confidence: 99%